Cultivar mixtures in panicle blast control in upland rice - Prabhu, Anne Sitarama (Pesquisa Agropecuaria Brasileira, 2014)
During 1984/85 and 1985/86 crop seasons field trials were conducted on cultivar mixtures as one of the alternative measures to restrict the panicle blast severities in upland rice. Two sets of mixtures, five each of early (Dourado Precoce, Guarani, IAC 25, IAC 165, IRAT 112) and medium duration (Amarelão, Araguaia, CNAx 104-13-34-2, IAC 47, IRAT 13) cultivars/lines exhibiting different degrees of susceptibility were compared with the individual components in relation to panicle blast and grain yield with and whithout chemical control. Three sprays of fungicide triciclazol (262 g/ha) were administered beginning from 5% heading. The average panicle blast severity of the treated and untreated plots of early duration cultivar mixture was signiticantly equal or less than the mean disease severity of its components. The performance of cultivar mixtures, in general, was inferior to the improved upland rice cultivars Guarani and Araguaia among the early and médium duration ones, respectively, in relation to panicle blast and grain yield.
Keywords: Pyricularia oryzae; Oryza sativa; varietal resistance; chemical control; fungicide; epidemiology.